Menafsirkan Makna Demokrasi Dalam Pemilihan Kepala Daerah: Kajian Kritis Terhadap Pemilihan Langsung dan Tidak Langsung - Warow, Gregorius Excelcis (Jurnal Suara Keadilan, 2025)
This paper discusses the quality of democracy in the context of regional head elections through the Regional People's Representative Council (DPRD) as an alternative to direct elections. Using normative legal research methods, this article examines the principles of democracy, the relationship between elections and people's sovereignty, and the constitutional basis in Article 18 of the 1945 Constitution of the Republic of Indonesia. The author questions whether the election mechanism by the DPRD can still be categorized as a democratic process. Through an analysis of regulatory dynamics, the phenomenon of money politics, and the Constitutional Court's ruling, this paper concludes that democracy is not only determined by the form of direct or indirect elections, but also by the application of the principles of honest, fair, free, and accountable elections. Therefore, it is important to reassess the forms of selection based on the effectiveness, efficiency, and integrity of the applicable system.Keywords: Demoracy Elections, DPRD, Regional Head Elections, Constitution